Synthetic strategy for preparation of a folate corrole DOTA heterobimetallic Cu–Gd complex as a potential bimodal contrast agent in medical imaging. Issue 51 (23rd December 2015) - Desbois, Nicolas; Michelin, Clément; Chang, Yi; Stupar, Vasile; Bonnaud, Mylène; Pacquelet, Sandrine; Gros, Claude P.
Graphical abstract: Abstract: An efficient sequential route to synthesize heterobimetallic complexes is reported herein. A folate, Cu corrole, Gd DOTA complex that addresses the requirements of a potential contrast agent (CA) for bimodal imaging (e.g., MRI/PET) is reported. The over-expression of the folate receptor in a variety of malignant tumors, along with its limited expression in healthy tissues, makes this an attractive tumor-specific molecular target. Synthesis of a bimetallic ligand potentially targeting the folate receptor, was easily achieved in only a few steps. Interestingly, preliminary studies showed that the relaxivity of the folic heterobimetallic derivative was higher in comparison to a clinically used Gd DOTA MRI contrast agent. Their radiocomplexes may be useful as an in vitro tool and for in vivo tumor diagnosis by using, for example, PET imaging.